Correlation Between AI Usage, Digital Literacy, and Students’ Self-Efficacy in Paragraph Writing - Afifah Khoirun Nisa; Anam Sutopo (General English Education, 2026)
This investigation examines the correlation between AI usage, digital literacy, and students’ self-efficacy in the Paragraph Writing course. In this study, digital literacy is conceptualized as students’ capacity to locate, critically assess, and responsibly utilize digital information. Meanwhile, AI usage focuses on AI usage to assist students in the writing process. This study employed a correlational design. The sample consisted of 109 students from the English Language Education Program at Muhammadiyah University of Surakarta, selected using random sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple and Spearman’s rank correlation analyses. The results indicated a significant correlation between AI usage and self-efficacy, with a correlation coefficient of 0.343, classified as low. Additionally, there is a significant correlation between digital literacy and self-efficacy, with a correlation coefficient of 0.630, classified as strong. The multiple correlation analysis showed that students’ self-efficacy and AI usage with digital literacy together are significantly correlated, with a correlation coefficient of 0.662. Digital literacy has a stronger correlation with self-efficacy than AI usage. Therefore, the use of AI needs to be balanced with digital literacy so that students are more confident in writing English paragraphs.